A Boron Alkylidene–Alkene Cycloaddition Reaction: Application to the Synthesis of Aphanamal. Issue 38 (9th August 2017) - Liu, Xun; Deaton, T. Maxwell; Haeffner, Fredrik; Morken, James P.
Abstract: We describe an unusual net [2+2] cycloaddition reaction between boron alkylidenes and unactivated alkenes. This reaction provides a new method for the construction of carbocyclic ring systems bearing versatile organoboronic esters. Aside from surveying the scope of this reaction, we provide details about the mechanistic underpinnings of this process, and examine its application to the synthesis of the natural product aphanamal. Abstract : Two plus two or not two plus two : Boron alkylidenes are generated by alkoxide‐induced deborylation of geminal bis(boronate)s. These alkene analogues undergo net [2+2] cycloaddition reactions with tethered alkenes, and the resulting boronate complexes can be trapped with electrophiles to generate substituted carbocyclic products.